Transabdominal ultrasound for the characterization and follow-up of cystic pancreatic lesions - Julian Seelig; Maria Heni; Max Seitzinger; Kien Vu Trung; Jürgen Feisthammel; Marcus Hollenbach; Robert Henker; Albrecht Hoffmeister; Jonas Rosendahl; Valentin Blank; Thomas Karlas (Scientific Reports)
Abstract Cystic pancreatic lesions (CPL) pose a diagnostic challenge due to their morphological diversity and malignant potential. Given the limited study data, transabdominal ultrasound (TAUS) is currently not established for either primary diagnostics or CPL monitoring. This study compared the diagnostic accuracy of TAUS in the assessment of CPL to that of the reference method, endoscopic ultrasound (EUS), to identify patient subgroups suitable for TAUS monitoring. In a monocentric, retrospective analysis, patients with CPL who underwent EUS and TAUS within six months from 01/2016 to 06/2022 were included. Univariate and multiple logistic regression analyses were used to identify determinants for the detection of CPL via TAUS. Cross-method morphological assessments were analysed, and a patient-specific algorithm for selecting the appropriate monitoring method was developed. Among 105 patients, CPL were detected by both EUS and TAUS in 90 patients (86%). Patients with “TAUS negative” CPL (n = 15) exhibited greater body mass indices (BMI, p = 0.002) and smaller CPL diameters (p = 0.043). The final multivariate model (BMI, age, CPL diameter) yielded an 85% accuracy in predicting CPL detectability by TAUS. TAUS could be a cost-effective and patient-friendly imaging method for the surveillance of CPL in selected patients.